An analysis on the efficiency of takaful and insurance companies in malaysia: a non-parametric approach - Md Saad, Norma (Society of Interdiciplinary Business Research, 2012)
This study examines the efficiency of general or non-life takaful and insurance industry in Malaysia during the period 2007 to 2009. In order to measure their efficiencies, the output-input data consists of a panel of 28 general or non-life takaful and insurance companies are used. The most commonly used non-parametric approach, namely, Data Envelopment Analysis (DEA) is adopted to measure the efficiency of the Malaysian takaful and insurance companies. In the DEA technique, efficiency is measured by the Malmquist index. The Malmquist efficiency measures are decomposed into two components: efficiency change and technical change index. Efficiency change is again decomposed into pure efficiency and scale efficiency. It is found that, on average, the TFP of the non-life takaful and insurance industry in Malaysia is mainly due efficiency change and the main sources of the efficiency change are both scale efficiency and pure efficiency.